Loss of mitochondrial aconitase promotes colorectal cancer progression via SCD1-mediated lipid remodeling - Xin You (Molecular Metabolism, 2021)
Objective: Mitochondrial aconitase (ACO2) is an essential enzyme that bridges the TCA cycle and lipid metabolism. However, its role in cancer development remains to be elucidated. The metabolic subtype of colorectal cancer (CRC) was recently established. We investigated ACO2's potential role in CRC progression through mediating metabolic alterations. Methods: We compared the mRNA and protein expression of ACO2 between paired CRC and non-tumor tissues from 353 patients. Correlations between ACO2 levels and clinicopathological features were examined. CRC cell lines with knockdown or overexpression of ACO2 were analyzed for cell proliferation and tumor growth. Metabolomics and stable isotope tracing analyses were used to study the metabolic alterations induced by loss of ACO2. Results: ACO2 decreased in >50% of CRC samples compared with matched non-tumor tissues. Decreased ACO2 levels correlated with advanced disease stage (P < 0.001) and shorter patient survival (P < 0.001). Knockdown of ACO2 in CRC cells promoted cell proliferation and tumor formation, while ectopic expression of ACO2 restrained tumor growth. Specifically, blockade of ACO2 caused a reduction in TCA cycle intermediates and suppression of mitochondrial oxidative phosphorylation, resulting in an increase in glycolysis and elevated citrate flux for fatty acid and lipid synthesis. Increased citrate flux induced upregulation of stearoyl-CoA desaturase (SCD1), which enhanced lipid desaturation in ACO2-deficent cells to favor colorectal cancer growth. Pharmacological inhibition of SCD selectively reduced tumor formation of CRC with ACO2 deficiency. Conclusions: Our study demonstrated that the rewiring metabolic pathway maintains CRC survival during compromised TCA cycles and characterized the therapeutic vulnerability of lipid desaturation in a meaningful subset of CRC with mitochondrial dysfunction.